Design strategy : challenges in wicked problem territory - Roberts, Nancy Charlotte (Cambridge, Massachusetts : The MIT Press, 2023)
"Problems without apparent solutions plague the contemporary world. Roberts proposes a new "Design Strategy" to approach these wicked problems and lays out its history and evolution, its process, principles, mindsets, skillsets and toolkits that inform and guide design practice"--
Landing in wicked problem territory -- Design strategy -- Designing in wicked problem territory -- Assessing the design strategy.
Includes bibliographical references and index.
Keywords: Design -- Philosophy; Problem solving